Rethinking Teaching: Conceptions of Learning Change and Learning Management - Menyani, Nourreddine (American Scientific Research Journal for Engineering, Technology, and Sciences, 2020)
Promoting excellence in teaching and boosting learners’ performance is and has always been the corner stone of education in general and in the foreign language classroom in particular. This article addresses the issue of the problematic way of teaching and catering for students with individual differences for a better interaction. Consequently, instructors are often confused and the questions of which teaching approach or learning theory to adopt often arises. The aim of this article is to explore how a teacher should teach in a foreign language classroom. Should a teacher adopt a learner-centered approach or a teacher-centered one? This paper also provides brief guidance to teachers on how to manage learners’ learning styles in the English language classroom for better instructional practices.